Politics and the social in world-class cities: Building a Shanghai model. (November 2015) - Samara, Tony Roshan
The 2010 World Expo in Shanghai provided a unique opportunity to examine emerging visions of utopian urbanism in the Global South, and the contradictions contained within them. The theme of the event was 'Better City, Better Life', and in its own promotional literature the Shanghai World Expo Coordinating Committee stressed the importance of sustainable, harmonious cities. The Expo was seen by many proponents as a way to educate the public about the opportunities and challenges cities face, and to identify and demonstrate solutions that harnessed the dynamism of urban space. At the same time, the Expo was itself a massive undertaking of urban redevelopment that dramatically reshaped parts of the downtown landscape and beyond. The aim of this article is to examine the vision of the World Expo that its proponents put forth, and to explore both inherent and extrinsic tensions between this vision and the trajectory of urban development.